Decentralization vs Cultural Centralization: The Paradox of Dangdut Koplo in Indonesian Popular Music - Aryandari, Citra (Mudra Jurnal Seni Budaya, 2026)
This study analyzes the paradox of decentralization and cultural centralization in contemporary Indonesian popular music through the case of dangdut koplo. Although post-2014 regional autonomy and digital technologies have expanded access to music production across Indonesia, this research shows the consolidation of a standardized Javanese koplo format as a dominant national template. Using multi-sited ethnography (2021–2023) in East Java, Makassar, Ambon, and East Kalimantan, combined with digital analysis of TikTok, YouTube, and Instagram, the study traces how rhythmic codification, platform circulation, and modular adaptation enable koplo to function as a musical lingua franca. Findings demonstrate that decentralized production infrastructures coexist with aesthetic convergence: standardized kendang patterns, visual framing, and mixing practices are widely reproduced, while regional melodic and vocal elements are layered onto a stable rhythmic structure. Drawing on Raymond Williams’ concept of cultural centrality, Homi K. Bhabha’s hybridity, and media ecology theory, this study proposes the concept of “standardized differentiation” to explain how structural uniformity coexists with patterned local variation. The research argues that digital and administrative decentralization reconfigure, rather than dissolve, cultural hierarchy in Indonesia’s contemporary music landscape.